Simulation Analysis of the Transient Temperature Field of Disc Brake Used in FSAE Racing Car - Zhang Jianhui; Yan Xianchao; Zhang Bing (Jixie chuandong)
The alternating transient temperature field will be caused during the braking of disc brake.The emergency braking condition under different speed of an FASE racing car is analyzed by using direct thermo-elastic coupling function of the ANSYS 14.0,the coupling effect between temperature field and stress field can be more actually reflected.Through the simulation analysis,the temperature distribution of brake disc and friction plate at different moments and the time course curve of the temperature on different nodes are gained.